My adventures as an illustrator : the definitive edition - Rockwell, Norman, 1894-1978; Rockwell, Thomas, 1933- (Abbeville Press Publishers, 2019)
"The wit, humanity, and many-sided talent of Norman Rockwell (1894-1978) are on full display in his classic autobiography, written with his son Tom Rockwell, himself an award-winning writer. The artist's New York City boyhood, his apprentice days at the Art Students League, his first fateful visit to the Saturday Evening Post, his adventures abroad, his move to rural Vermont - all are recounted with a mix of sharp observation and self-deprecating humor. Throughout Rockwell invites the reader into his creative process: he introduces his favorite models, candidly reveals his biggest flops, and documents the creation of a Post cover step by step. This Definitive Edition - edited by Abigail Rockwell, the artist's granddaughter - restores the original 1960 text of My Adventures as an Illustrator, as well as the playful vignettes that Rockwell drew to head each chapter. Thanks in large part to a massive image digitization effort undertaken by the Norman Rockwell Museum, it is also illustrated with 170 of Rockwell's paintings and drawings, some of them rarely - or never - seen before. An introduction by Abigail Rockwell brings to light new facts about the artist's life and work, and an illustrated chronology, prepared by the Norman Rockwell Museum, serves as a valuable reference. This attractive volume is the essential source on the life of Norman Rockwell, and delightful reading for anyone who enjoys his art." -- inside front cover.